Relationship of urinary bisphenol A in childhood on thyroid hormone function in adolescents: a cohort study - Jung Eun Choi; Eun Jeong Choi; Seonhwa Lee; Bohyun Park; Hye Ah Lee; Young Sun Hong; Eunhee Ha; Hae Soon Kim; Hyesook Park (PLoS ONE, 2025)
Background Bisphenol A (BPA) is a type of endocrine-disrupting chemical utilized in the production of plastics like epoxy resins and polycarbonate polymers. BPA exhibits weak estrogenic and potent anti-androgenic effects, and prior research has linked it to disturbances in thyroid function. This study aims to assess the potential association between early childhood exposure to urinary bisphenol A and thyroid hormone levels in pubertal children from Korea. Methods Participants were drawn from the Ewha Birth and Growth Cohort Study, encompassing individuals who visited Ewha Women’s Mokdong Hospital between 2001 and 2005. The concentration of urinary BPA was repeatedly measured for each subject at ages 3–5 years and 7–9 years. Serum levels of free triiothyronine (T3), free thyroxine (T4), and thyroid-stimulating hormone (TSH) were measured at ages 10–12 years in a subgroup of 128 out of 164 subjects who had undergone repeated BPA concentration measurements. We utilized the SAS program to analyze possible links between childhood exposure to BPA and thyroid hormone function in adolescence. Additionally, we explored how exposure to BPA during two specific periods influenced changes in thyroid hormone levels. Results The study observed that urinary BPA levels at ages 3–5 years were not notably linked to thyroid hormone levels in adolescents aged 10–12 years. However, BPA levels at ages 7–9 years were significantly associated with free T3 levels in girls aged 10–12 years. Conversely, exposure to BPA did not result in significant differences in thyroid hormone levels among boys. The study did not find statistically significant connections between levels of urinary BPA and the other thyroid hormones, specifically TSH and free T4. There was a significant decrease in the concentration of free T3 in girls with higher BPA concentrations. Conclusions BPA exposure in childhood affects thyroid function in adolescent girls. This relationship may contribute to an increased prevalence of thyroid disorders in adolescents due to environmental influences.